Grafted stone pine plantations for cone production: trials on Pinus pinea and Pinus halepensis rootstocks from Tunisia and Spain. - Piqué M.; Coello J.; Ammari Y.; Aletà N.; Sghaier T.; Mutke S. (Mediterranean pine nuts from forests and plantations, 2017)
Grafted Pinus pinea plantations for early and abundant cone production are a good chance to restore and promote rural Mediterranean areas generating both economical (pine nut production) and ecological(soil protection) benefits. Grafting P. pinea on P. halepensis rootstocks can result in even more interesting outcomes because they can be used in degraded, dry and calcareous sites, which can hardly support any other relevant forest production. In the framework of a project supported by the Spanish Agency for International Development and Cooperation (AECID), implemented in Tunisia and Spain, we produced grafted plants using two types of stock (P. pinea and P. halepensis) from known provenances in Spain and Tunisia. During autumn-winter 2011-2012, field trials were established in both countries with the aim of studying the adaptation,development and cone production of the grafted plantations. In Spain and Tunisia, there are respectively five and six grafted field trials, using scions of four Spanish elite clones and nine root-stock provenances (five from Tunisia, four from Spain) of P. pinea and P. halepensis.In these plantations the basal tree diameter, total tree height, height until grafting point, graft diameter, success of grafting and cone produc tion were measured. Factors influencing the grafting success, trees development and cone production we re studied, namely stock species,stock provenance, grafting type and field site conditions.
2. International Meeting on Mediterranean Stone Pine for Agroforestry : AgroPine2016, 2016/05/18-20, Oeiras (Portugal)